Preliminary studies of rosmarinic acid microencapsulation with chitosan and modified chitosan for topical delivery - F. Casanova (2016)
Rosmarinic acid (RA) is a naturally occurring phenolic compound with antioxidant, anti-carcinogenic and anti-inflammatory activities, amongst others, and is therefore a compound of interest for cosmetic applications. However RA instability, poor solubility in water and low partition coefficient constrain its transport across biological barriers, the inclusion in a cosmetic formulation and the efficacy of the antioxidant. The purpose of this study was to prepare and characterize chitosan and modified chitosan microparticles containing RA, as means to overcome its limitation in cosmetic formulations, as well as to study the controlled release of RA from the particles under cosmetic formulation conditions. Rosmarinic acid was encapsulated into chitosan and modified chitosan microparticles by a spray drying process. The prepared RA-loaded microparticles were analysed by scanning electron microscopy (SEM) for particle morphology analysis and laser granulometry to determine particle size distribution. The product yield (quantity of powder recovered in relation to the amount of raw materials used) was also determined. The study of rosmarinic acid release profiles from the obtained micropartides was performed in water (pH 5.5) and coconut oil, to simulate vehicles for incorporation of microparticles for skin delivery in cosmetic formulations. The release analysis was accomplished by evaluating the amount of rosmarinic acid released from the particles over a specified time using a UV-Vis spectrometry method. Product yields of 42.6% and 39.8% were obtained for chitosan and modified chitosan particles, respectively. Spherical microparticles, with a regular shape and an average diameter (in differential volume) of 4.2 mu m and 7.7 mu m were obtained either using chitosan or modified chitosan as encapsulating agent. Controlled release studies of RA showed that modified chitosan particles exhibited a slower release in oil than in water. Chitosan particles showed a faster release in both mediums. The results in this study are significant and prove the success of RA microencapsulation by a spray-drying technique for a topical delivery through cosmetic formulations (aqueous and oily) using chitosan-based microparticles. (C) 2016 Published by Elsevier B.V.